Security-Enhanced User Pairing for MISO-NOMA Downlink Transmission - Tantan Zhao; Guobing Li; Guomei Zhang; Chun-Xia Zhang (2018 IEEE Global Communications Conference (GLOBECOM), 2018)
In this paper the transmission security for multiuser multi-input single-output (MU-MISO)- Non-orthogonal multiple access (NOMA) downlink transmission is studied for untrusted users. We propose a security-enhanced user pairing scheme under the constraints of weak security to achieve high spectrum efficiency as well as weak system secrecy. We first formulate a sum-rate maximization problem for NOMA subject to weak security constraints, and reformulate the weak security requirement into constraints of the average bit error rate (BER) at any undesired user. Then we decompose the original optimization problem into a security-guaranteed user pairing problem and a conventional sum-rate maximization problem for NOMA, which is eventually solved by jointly downlink beamforming and power allocation. Simulation results compare the proposed NOMA scheme with zero-forcing (ZF) and the conventional MU-MISO beamforming, and reveal the performance gain of the proposed NOMA scheme in secrecy sum-rate.